Quantifying the Atmospheric CO2 Forcing Effect on Surface Ocean pCO2 in the North Pacific Subtropical Gyre in the Past Two Decades - Chen, Shuangling; Sutton, Adrienne J.; Hu, Chuanmin; Chai, Fei (Frontiers in Marine Science, 2021)
Despite the well-recognized importance in understanding the long term impact of anthropogenic release of atmospheric CO2 (its partial pressure named as pCO2air) on surface seawater pCO2 (pCO2sw), it has been difficult to quantify the trends or changing rates of pCO2sw driven by increasing atmospheric CO2 forcing (pCO2swatm_forced) due to its combination with the natural variability of pCO2sw (pCO2swnat_forced) and the requirement of long time series data records. Here, using a novel satellite-based pCO2sw model with inputs of ocean color and other ancillary data between 2002 and 2019, we address this challenge for a mooring station at the Hawaii Ocean Time-series Station in the North Pacific subtropical gyre. Specifically, using the developed pCO2sw model, we differentiated and separately quantified the interannual-decadal trends of pCO2swnat_forced and pCO2swatm_forced. Between 2002 and 2019, both pCO2sw and pCO2air show significant increases at rates of 1.7 ± 0.1 μatm yr–1 and 2.2 ± 0.1 μatm yr–1, respectively. Correspondingly, the changing rate in pCO2swnat_forced is mainly driven by large scale forcing such as Pacific Decadal Oscillation, with a negative rate (-0.5 ± 0.2 μatm yr–1) and a positive rate (0.6 ± 0.3 μatm yr–1) before and after 2013. The pCO2swatm_forced shows a smaller increasing rate of 1.4 ± 0.1 μatm yr–1 than that of the modeled pCO2sw, varying in different time intervals in response to the variations in atmospheric pCO2. The findings of decoupled trends in pCO2swatm_forced and pCO2swnat_forced highlight the necessity to differentiate the two toward a better understanding of the long term oceanic absorption of anthropogenic CO2 and the anthropogenic impact on the changing surface ocean carbonic chemistry.